Rancang Bangun Sistem Pengelolaan Barang Milik Negara Berbasis QR Code - Ahmad Hamim THohari; Febrianto Hidayat; Maidel Fani; Nelmiawati Nelmiawati (Politeknik Negeri Batam, 2022)
BMN has meaning of all assets acquired from APBN expenses or other legal acquisitions. Politeknik Negeri Batam is required to manage, use and maintain in order to get benefit from these assets. Utilization of technology is an absolute solution in this management. The current management system works conventionally whereby an inventory number is printed on a label in each item. A difficulty found when it uses to track and check for inventory during daily usage or maintenance. A BMN QR code-based system is proposed which consists of two applications, namely web and mobile. The application was developed using an iterative prototyping method in order to get speed and accuracy according to user needs. The mobile application uses to quickly access goods data by scanning the item code, while a web application with a QR Code generator used to manage item data and create a QR Code based on the code item. Mobile applications were developed using the Ionic Framework, while web applications were built with AngularJS. The application testing results show that all defined functionalities can function and meet user needs.